Studi Literatur Penerapan Pembelajaran Berdiferensiasi Terhadap Keterampilan 4C Pada Siswa Usia SD - Adelia, Jessica Triuli; Sarifah, Iva; Yudha, Chrisnaji Banindra (Universitas Negeri Makassar, 2024)
The implementation of differentiated learning should ensure that every student is given equal opportunities for effective learning without any exceptions. This research aims to systematically review the literature on how differentiated learning is applied to 4C skills in elementary school students. The research method used is a literature study. Data collection comes from previous scientific articles published in 2020-2024 by setting keywords namely learning, differentiated, and elementary school. Articles were obtained through Publish or Perish. Differentiated learning really requires the role of teachers in making diagnostic assessments to map student's initial abilities, interests, and learning styles. Teachers can consider the type of differentiated learning based on the assessment results. There are 4 types of differentiated learning that can be applied to develop 4C skills in elementary school students, namely differentiation of content, process, product, and learning environment. The implementation of differentiated learning that contains activities based on student's needs can develop critical thinking, communication, collaboration and creative thinking skills of elementary-age students.